Metaloproteinases da matriz 2 e 9 em coelhos com cardiomiopatia induzida pela doxorrubicina - Silva, Sheila Nogueira Saraiva da [UNESP] (2014)
Doxorubicin is a chemotherapy agent frequently used in oncology patients. Its cardiotoxicity is related to several cellular mechanisms, including necrosis and apoptosis. Some studies have ascribed a role to matrix metalloproteinases and their inhibitors in the cardiotoxicity induced by doxorubicin. Therefore, this research was aimed at evaluating the plasma and myocardial activities of matrix metalloproteinases 2 and 9 in rabbits with doxorubicin-induced cardiomyopathy, searching for a correlation between them and the cardiac remodeling attributable to such disease. The animals were assigned into two groups: control (n=10) and doxorubicin (n=15). The plasmatic and myocardial activities were analyzed through the method of zymography. Only the inactive MMPs (pro-MMP) have been identified in the blood samples. The plasma pro-MMP-2 was documented in both control and doxurubicin animals from T0 to T45. On the contrary, the pro-MMP-9 was found in some samples of control and doxurubicin groups, especially at T30 and T45, although only weak bands have been demonstrated. A significant difference was shown to occur in pro-MMPs-2 and 9 along time. Correlation tests between the plasma pro-MMPs and the echocardiographic data demonstrated significant results. At T0 a correlation was found between A’lat and pro-MMP-2; at T15 correlations were documented between pro-MMP-2 and the parameters PEP and TEI; at T30 a correlation was identified between pro-MMP-9 and PLVE%; lastly, at T45 correlations have been observed between pro-MMP-2 and the parameters LVIDs, LVIDd, IVSs e Emitral/E’sep, as well as between pro-MMP-9 and LVET. Only the pro-MMP-2 was documented at the myocardium, although no significant difference between groups could be demonstrated. The plasmatic activity of the MMPs, specially the pro-MMP2, could be related to the morphofunctional alterations of the induced cardiomyopathy, and that there was no correlation between the plasmatic ...